2015
DOI: 10.1063/1.4923221
|View full text |Cite
|
Sign up to set email alerts
|

Wave packet propagation across barriers by semiclassical initial value methods

Abstract: Semiclassical initial value representation (IVR) formulas for the propagator have difficulty describing tunneling through barriers. A key reason is that these formulas do not automatically reduce, in the classical limit, to the version of the Van Vleck-Gutzwiller (VVG) propagator required to treat barrier tunneling, which involves trajectories that have complex initial conditions and that follow paths in complex time. In this work, a simple IVR expression, that has the correct tunneling form in the classical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…References [6,19,20] showed that complex time propagation, along with the correct choice of complex time contours, leads to accurate wavepacket reconstruction for barrier transmission problems. Similarly, the oscillatory system studied in the following section is strongly influenced by the dynamical singularities, and the use of complex time integration contours is required to obtain accurate results.…”
Section: Complex Time Propagationmentioning
confidence: 99%
“…References [6,19,20] showed that complex time propagation, along with the correct choice of complex time contours, leads to accurate wavepacket reconstruction for barrier transmission problems. Similarly, the oscillatory system studied in the following section is strongly influenced by the dynamical singularities, and the use of complex time integration contours is required to obtain accurate results.…”
Section: Complex Time Propagationmentioning
confidence: 99%
“…This not only implies the existence of randomness in a quantum system, but also discloses that the random motion occurs in complex space. Numerous studies with the complex initial condition and the random property have been discussed [23][24][25]. A stochastic interpretation of quantum mechanics is proposed which regards the random motion as a nature property of the quantum world not the interference made by the measurement devices [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…14,20,24 A separate publication will give more details of the implementation and the phase space geometry of the caustics in the four prototypical potentials.…”
Section: Application To Wavepacket Reconstructionmentioning
confidence: 99%
“…However the PED requires comparison of trajectory pairs which can only be found numerically via a root search in the complex trajectory manifold. In continuous time dynamics such a root search is quite challenging and has been successful so far only for relatively short times [5,[11][12][13][14]. Long time dynamics where the trajectory manifold is plagued by a multitude of caustics, remains elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation